Reducing environmental uncertainty: How high performance work systems moderate the resource dependence‐firm performance relationship. (9th November 2016) - Bendickson, Josh; Gur, Furkan A.; Taylor, Erik C.
Abstract: Firm performance is a major concern for all organizations and involves a multitude of antecedents. Reducing environmental uncertainty and dependency through the use of strategic actions in the resource dependency theory (RDT) framework and enhancing work practices through high performance work systems (HPWS) lead to higher levels of firm performance. We reveal the interconnectivity between RDT and HPWS and develop propositions as to how components of HPWS positively moderate the relationship between firm performance and the environmental uncertainty‐reducing strategic actions proposed by RDT such as mergers and acquisitions, joint ventures, boards of directors, political action, and executive succession. Copyright © 2016 ASAC. Published by John Wiley & Sons, Ltd.